PEMANFAATAN BUKU TEKS OLEH GURU EKONOMI SMA NEGERI SE-KABUPATEN OGAN ILIR - Yunita Leni Utari; Deskoni; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
This study discusses the use of textbooks by economics teacher based on curriculum 2013 high schools in Ogan Ilir. The formulation of the research problem are